# Tell which statement is not true. 1. If x+2/x = 5+y/5, then 2/x = y/5 2. If x/3 = y/4, then x/y = 4/3 3. If x+3/4 = y/5, then x+3/y =4/5 4.If x-4/4 = 3-y/y, then x/4 = 3/y

*print*Print*list*Cite

For each statement, use cross-multiplication and solve for x for both the "if" clause and the "then" clause.

**Statement 1:**

If (x + 2) / x = (5 + y) / 5, then 2 / x = y / 5**IF...**

5(x + 2) = x(5 + y)

5x + 10 = 5x + xy

5x + 10 + (-5x) = 5x + xy + (-5x)

10 = xy

x = 10/y**THEN...**

2 / x = y / 5

2 * 5 = x * y

10 = xy

x = 10/y**Statement 1 is true.**

**Statement 2:**

If x / 3 = y / 4, then x / y = 4 / 3 **IF...**

x / 3 = y / 4

4 * x = 3 * y

4x = 3y

4x / 4 = 3y / 4

x = 3y / 4**THEN...**

x / y = 4 / 3

3 * x = 4 * y

3x = 4y

3x / 3 = 4y / 3

x = 4y / 3**Statement 2 is false.**

**Statement 3:**

If (x + 3) / 4 = y / 5, then (x + 3) / y = 4 / 5 **IF...**

5(x + 3) = 4 * y

5x + 15 = 4y

5x + 15 + (-15) = 4y + (-15)

5x = 4y - 15

5x / 5 = (4y - 15) / 5

x = 0.8y - 3**THEN...**

(x + 3) / y = 4 / 5

5(x + 3) = 4 * y

5x + 15 = 4y

5x + 15 + (-15) = 4y + (-15)

5x = 4y - 15

5x / 5 = (4y - 15) / 5

x = 0.8y - 3**Statement 3 is true.**

**Statement 4:**

If (x - 4) / 4 = (3 - y) / y, then x / 4 = 3 / y**IF...**

(x - 4) / 4 = (3 - y) / y

y(x - 4) = 4(3 - y)

xy - 4y = 12 - 4y

xy - 4y + 4y = 12 - 4y + 4y

xy = 12

xy / y = 12 / y

x = 12 / y **THEN...**

x / 4 = 3 / y

x * y = 4 * 3

xy = 12

xy / y = 12 / y

x = 12 / y**Statement 4 is true.**

**The statement that is not true is STATEMENT 2.**

Answer is No.2.

Solution:

x/3=y/4

When cross multiplying, we get

x/y=3/4

Hence No.2 is not true.